Síntese das reflexões da reunião sobre ética em pesquisa qualitativa em Saúde, Guarujá, SP Synthesis of the reflections of the meeting on ethics in qualitative health research, Guarujá, São Paulo State - Iara Coelho Zito Guerriero (Ciência & Saúde Coletiva, 2008)
Este artigo apresenta uma síntese do relatório elaborado coletivamente na reunião sobre Ética em Pesquisa Qualitativa em Saúde, realizada no Guarujá, de 28 a 30 de agosto de 2006. Organizada pelo Comitê de Ética em Pesquisa da Secretaria Municipal de Saúde de São Paulo- CEP/SMS, com apoio do Special Programme for Research and Training in Tropical Diseases(TDR), sponsored by UNICEF/UNDP/World Bank/WHO, a reunião apontou a necessidade de revisar as diretrizes brasileiras para análise dos aspectos éticos das pesquisas qualitativas em saúde. This article presents a synthesis of the report collectively elaborated in the meeting on Ethics in Qualitative Health Research, which took place in Guarujá, São Paulo State, from August 28 to 30, in 2006. The meeting was organized by the Ethical Committee of the Municipal Health Office of São Paulo, supported by the Special Programme for Research and Training in Tropical Diseases (TDR), sponsored by UNICEF/UNDP/World Bank/WHO and stressed the need to review the Brazilian guidelines for the analysis of the ethical aspects of qualitative health research.